Incertezas na decisão estratégica de investimento na geração de energia elétrica - Patricia Bernardes (2003)
The main focus of this work was to diagnose and to analyze, under the great consumer's of electric power of the State of Minas Gerais point of view, their uncertainties associated to the strategic decision to invest in electric power generation. The survey used a pre-test questionnaire, a final structured questionnaire and focus groups sessions with a select group of five specialists in the electric power section. The questionnairewas applied to the states greatest energy consumers in the process industry, specifically in the sub sectors of metallurgy, mining, aluminum, cement, paper, cellulose, textile, sugar and alcohol. Answers of thirty-two companies were obtained in a total of fifty responders, either in charge professionals or personnel with in-depth knowledge of electric power politics of the companies in which they are employed. The elaboration of the researchs instruments was based, especially, in the theories on strategy, economical base institutionalism and in corporate governance in a wider scope. We also pursued a bibliographical research on the paths of the electric power sector, consulting and analyzing documents on the subject. The collected data in the questionnaires were treated using descriptive statistics use and multivariate analysis. We attempted to make a comparison between the qualitative and quantitative outcomes, which has shown the importance of the rules in the great electric power consumer's strategic decision to invest in electric power generation. Briefly, the main results of this work were the elaboration of a factorial model of uncertainties associated to the great consumer's of energy strategic decision to invest in electric power generation, a conclusive consideration about the States oscillation between the role of producer and regulator or the inconclusiveness of the electric power sector regulation. An uncertainty indicator was elaborated, with four dimensions tested on their reliability and they displayed internal consistency between the items and also the confirmation, by the quantitative instruments, that the environmental, institutional and corporate governance uncertainties are important to the great electric power consumer's strategic decision to invest in electric power generation. It was also diagnosed the importance of the implementation and the increase of alternative sources of electric power generation of which Brazil holds comparative advantages, due to the climate and/or technology domain. Finally, it leads to the conclusion that the reorganization of the electric power sector, which began in the mid 90s, does not have financing sources and a regulation able to stimulate the growth of electric power generation and to avoid a new supplying crisis in the next few years. Among the main difficulties for the sectors growth, we can mention the environmental legislation, the need of evaluation of the financial results obtained from the investments and the gas price increase, mostly as a consequence of the depreciation of the Real after the second semester of 2002.